IS APPRECIATION PROFIT? - Schmidt, Fritz (The Accounting Review, 1931)
The question, whether appreciation is a profit, is not merely the concern of bookkeepers. It is a fundamental point of both business and general economic theory. According as this question is answered there will have to be differences in concepts which prevail in business it regarding profit, capitalized value, price policy, balance sheet theory, tax law and financing. The business man cannot neglect the significance of this question as he is accustomed to do in matters of pure theory on the ground that is far removed from his concern. What he reports as profit to his stockholders depends upon his interpretation of this question. Wage policies are also affected and, of course, the computation of income taxes. Varying concepts of profit will have an even more distinct relation to economic theory. it is clear that the concepts of rent, interest, market value, price, income and capital must vary according to whether one considers as income only the real product produced within a certain period, or whether income is regarded as the surplus increment of value between two points of time. This is, therefore, a basic question of economic science and deserves careful attention.